Iron transformation mediates phosphate retention across a permafrost thaw gradient - Maximilian Barczok; Chelsea Smith; Lauren Kinsman-Costello; Monique Patzner; Casey Bryce; Andreas Kappler; David Singer; Elizabeth Herndon (Communications Earth & Environment)
Abstract Phosphorus limits primary productivity in many (Sub-)Arctic ecosystems and may constrain biological carbon sequestration. Iron (III) oxides strongly bind phosphate in soils but can dissolve under flooded, reducing conditions induced by permafrost thaw and ground collapse. The ability for iron to regulate phosphate storage and solubility in thawing permafrost landscapes remains unclear. Here, iron-rich sediments containing iron oxides and organic-bound iron were incubated with or without added phosphate in soils along a permafrost thaw gradient to evaluate how iron-phosphate associations respond to thaw-induced redox shifts. Iron oxides partially dissolved and released sorbed phosphate when incubated in soils underlain by degraded permafrost. Iron complexed by organic matter remained stable but provided no phosphate binding capacity. Phosphate addition enhanced iron oxide dissolution and phosphorus concentrations in associated microbial biomass. Our study demonstrates that the capacity for iron oxides to immobilize and retain phosphate in permafrost peatlands decreases with permafrost thaw.